(untitled) - Daft, Richard L. (Fort Worth, 1997)
This edition aims to equip students with a solid foundation in the essentials of an introductory management class and introduces students to current trends, theories and issues in the dynamic field of management. Real-world examples are featured in the text.
Keywords: Quản lý công nghiệp,Industrial management